DESIGN OF RETAINING WALLS ON THE NORTHERN AND EASTERN SIDES FOR SEAWATER INTAKE OF JAWA 9 & 10 SURALAYA STEAM POWER PLANT - Adz - Dzikro, Ibadurrahman
The Jawa 9 & 10 Suralaya steam power plant is one of the main steam power plants in Indonesia, with a capacity of up to 4,025 megawatts. The use of seawater through sea water intake is essential in this type of power plant. The construction of the sea water intake requires deep excavation, which can disrupt the stability of the surrounding soil. Therefore, retaining walls are necessary as structures that can withstand the lateral pressure of the soil and maintain stability. This Final Project discusses the design of retaining walls on the northern and eastern sides of the Jawa 9 & 10 Suralaya steam power plant. The design must meet the criteria for wall design, slope stability, and wall reinforcement. The design of the retaining walls begins with the processing of soil data obtained from the field and laboratory tests to determine the existing soil parameters. Subsequently, iterations are performed to obtain the initial design of the retaining walls. Iterations are conducted using manual calculations using the hinge method and GTS NX software. The soil modeling is performed using the plane strain method, and the soil is modeled using the Mohr-Coulomb model. The wall's safety factor and slope stability are evaluated using the strength reduction method (SRM) concept. The design verification of the reinforcement should be evaluated through field testing, including investigation tests, conformity tests, and acceptance tests. Based on the iterations and modeling performed, the design results of the retaining walls consist of diaphragm walls with a thickness of 0.6 m, a height of 26 m, and three wall reinforcements. The reinforcement used is soil anchors using prestressed steel strands with a diameter of 15 mm ASTM A416. The reinforcements are located at elevations of -2 m, -4 m, and -9 m. The reinforcement consists of 7 strands with pre-stressing forces for anchors 1, 2, and 3 of 204 kN, 628 kN, and 728 kN, respectively.